2007
DOI: 10.1007/s11434-007-0184-2
|View full text |Cite
|
Sign up to set email alerts
|

Concentration level and distribution of polycyclic aromatic hydrocarbons in soil and grass around Mt. Qomolangma, China

Abstract: High mountains may serve as a condenser for persistent organic pollutants. In the present study, soil and grass samples from Mt. Qomolangma region, China were collected from 4600 to 5620 m a.s.l and were analyzed for polycyclic aromatic hydrocarbons (PAHs) to determine if they are concentrated at colder, more elevated sites and to evaluate their possible resources and fractionation. The total PAHs concentration in soil samples was < 600 ng g −1 , the critical value to differentiate PAHs levels in remote and ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 43 publications
8
29
0
Order By: Relevance
“…The mean concentrations of Acy and Phe in soils from the NSHC were 31 and 28 ng/g, dw, which accounted for 25% and 23% of the mean concentration of total PAHs, respectively (Table 1). This result is consistent with results reported by Wang et al (2007). However, 27% of the soil samples from the NSHC had concentrations of Phe that were significantly greater than the maximum permissible concentration of 50 ng/g, dw, suggested by the Netherlands.…”
Section: Concentrations Of Pahs In Soilsupporting
confidence: 92%
See 2 more Smart Citations
“…The mean concentrations of Acy and Phe in soils from the NSHC were 31 and 28 ng/g, dw, which accounted for 25% and 23% of the mean concentration of total PAHs, respectively (Table 1). This result is consistent with results reported by Wang et al (2007). However, 27% of the soil samples from the NSHC had concentrations of Phe that were significantly greater than the maximum permissible concentration of 50 ng/g, dw, suggested by the Netherlands.…”
Section: Concentrations Of Pahs In Soilsupporting
confidence: 92%
“…Based on above observations, it is easy to conclude that the significant and positive relationships between S 16 PAH concentrations and altitude occurred in our study because concentrations of LMW-PAHs contributed more than 70% to those of S 16 PAHs in both China and Nepal (Table 1). This result was also supported by Wang et al (2007) who suggested that concentrations of total and 3-ring PAHs in Himalayan soils were positively correlated with altitude (4700e5600 m), whereas no correlation was found for HMW-PAHs.…”
Section: Altitudesupporting
confidence: 71%
See 1 more Smart Citation
“…PAHs were even detected in surface soil in high-mountain regions (e.g., Mt. Qomolangma,8,844.3 m a.s.l) and vast remote areas (e.g., the Qinghai-Tibetan Plateau), which indicated the national wide pollution of PAHs in China (Tao et al 2011;Wang et al 2007). In addition to local and national influence across China, PAH pollution can also influence the neighbor countries and regions through long-range atmospheric transport (Inomata et al 2012;Lang et al 2008;Primbs et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…POPs are widely distributed in the environment [1, 4,5], which are harmful to human health by breathing, drinking and food chain [6]. Therefore, the interfacial behavior, environmental transport, health effects, pollution control and restoration of POPs are widely concerned [610].…”
mentioning
confidence: 99%